Social Justice’s Manifestation: The Relation Between Limited Companies and Small and Medium Enterprises - I Gede Agus Kurniawan (Universitas Islam Balitar, Blitar, 2023)
Social justice is an important pillar of Indonesia's constitutional identity. In this case, every law relating to the Indonesian economy is required to reflect the substance of social justice. One aspect that must pay attention to aspects of social justice is related to the formation of a Limited Liability Company or Perseroan Terbatas (PT). This research aims to find the urgency of the manifestation of social justice in the formation of PT before and after revision. This research is normative legal research which has an orientation towards the study of legal norms and rules. This research is based on legal issues, namely the social justice aspect in the legal policy of facilitating Small and Medium Enterprises (SMEs) in establishing PT. The legal materials in this research include primary legal materials and secondary legal materials, as well as non-legal materials. The approaches in this research are the statutory regulatory approach and the conceptual approach. The research results confirm that the essence of the revised PT provisions in the Job Creation Law is to allow PTs to be formed by business, micro, and small business legal entities. The essence of social justice seeks to improve the welfare of all levels of Indonesian society. In fact, this has been facilitated by the revision of the provisions of the Job Creation Law and its derivative regulations so that PTs are not only dominated by investors but can also empower SMEs.